2002
DOI: 10.1089/10966210252785079
|View full text |Cite
|
Sign up to set email alerts
|

Should There be a Choice for Cardiopulmonary Resuscitation When Death is Expected? Revisiting an Old Idea Whose Time is Yet to Come

Abstract: Since closed chest cardiac massage was introduced in 1960, the notion that cardiopulmonary resuscitation (CPR) attempts are not appropriate for all patients has been consistent. Over the years, leading authorities have clearly articulated that for patients who are dying irreversibly and expectedly medical decisions for do-not-resuscitate (DNR) orders should be made by physicians, because in such cases CPR attempts are not indicated. Physicians are not obligated to and should not offer or provide useless treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 67 publications
0
24
0
Order By: Relevance
“…This may reflect the view that the DNR order is a medical decision regarding a treatment with medical indications that do not have to be discussed with the patient or family if the treatment is thought to be inappropriate for the patient. [53436] In keeping with local guidelines, the Scottish integrated policy on decision making and communication of DNR orders states that where CPR is unlikely to have a medically successful outcome, it should not be attempted and it is “an unnecessary and cruel burden” to ask patients and relevant others to decide about CPR when it is not a treatment option. [353738]…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect the view that the DNR order is a medical decision regarding a treatment with medical indications that do not have to be discussed with the patient or family if the treatment is thought to be inappropriate for the patient. [53436] In keeping with local guidelines, the Scottish integrated policy on decision making and communication of DNR orders states that where CPR is unlikely to have a medically successful outcome, it should not be attempted and it is “an unnecessary and cruel burden” to ask patients and relevant others to decide about CPR when it is not a treatment option. [353738]…”
Section: Discussionmentioning
confidence: 99%
“…A joint statement from the British Medical Association, the Royal College of Nursing and the UK Resuscitation council recommended that resuscitation status should be discussed with patients before they get critically ill 6. Others have suggested that patients do not need to be involved in the decision although they should be told of the health professionals’ decision 7. We believe that most healthcare professionals feel that patients should be involved, if that is possible, but in practice discussions are often left until patients are too ill to be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Some have argued that the DNR decision is a medical decision and that doctors need neither offer or discuss CPR nor obtain patient consent for recording a DNR order (Ditillo, 2002;Marik & Zaloga, 2001). Nonetheless, as with all decisions referring to individual patients, the dominant principle guiding medical practice regarding DNR orders is that of patient autonomy (Burns et al, 2003).…”
mentioning
confidence: 99%